2018
DOI: 10.1038/sdata.2018.75
|View full text |Cite
|
Sign up to set email alerts
|

Wide-field corneal subbasal nerve plexus mosaics in age-controlled healthy and type 2 diabetes populations

Abstract: A dense nerve plexus in the clear outer window of the eye, the cornea, can be imaged in vivo to enable non-invasive monitoring of peripheral nerve degeneration in diabetes. However, a limited field of view of corneal nerves, operator-dependent image quality, and subjective image sampling methods have led to difficulty in establishing robust diagnostic measures relating to the progression of diabetes and its complications. Here, we use machine-based algorithms to provide wide-area mosaics of the cornea’s subbas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 42 publications
0
46
0
Order By: Relevance
“…Scale bar = 0.5 mm. The entire set of original high-resolution images of sub-basal plexi from the cohort is freely available 32 .
Figure 4 Sub-basal nerve plexus mosaic from the central cornea taken from the left eye of a subject with NGT.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scale bar = 0.5 mm. The entire set of original high-resolution images of sub-basal plexi from the cohort is freely available 32 .
Figure 4 Sub-basal nerve plexus mosaic from the central cornea taken from the left eye of a subject with NGT.
…”
Section: Resultsmentioning
confidence: 99%
“…As part of ophthalmic examinations in 2014, the central cornea in both eyes of all study subjects was imaged by in vivo confocal microscopy (IVCM) using a Heidelberg Retinal Tomograph 3 with Rostock cornea module (HRT3-RCM, Heidelberg Engineering, Heidelberg, Germany). Details of the imaging procedure have been described elsewhere 32 . Briefly, a drop of ophthalmic tear gel (Tear Gel carbomer 0.3%, Thea Pharmaceuticals, France) was used as coupling medium between the microscope objective lens and the corneal surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 The diagnostic ability of IVCCM may be further enhanced by assessing the inferior whorl or using wide-area mosaics, which take into account both proximal and distal corneal nerve morphology. 30,31 Multiple pathogenetic mechanisms, including advanced glycation, increased flux through the sorbitol pathway, and oxidative stress, have been implicated in the development of diabetic neuropathy. 32 Experimental studies using a combination of menhaden oil, a-lipoic acid, and enalapril have been shown to ameliorate oxidative and inflammatory stress and improve distal corneal nerve morphology.…”
Section: Discussionmentioning
confidence: 99%
“…First, CCM parameters were estimated on a CCM mosaic of images generated by custom‐made software, rather than single images as per previously validated methodology. It is unknown if the approach is of diagnostic value, especially in cross‐sectional observational studies . Second, the CCM mosaic was compared to single skin biopsy sections, which may have introduced an estimation bias.…”
Section: Corneal Confocal Microscopy For Peripheral Neuropathiesmentioning
confidence: 99%